PENCIPTAAN ALAM SEMESTA DALAM AL-QUR’AN DAN TANAKH (YAHUDI) : PENDEKATAN INTERTEKSTUALITAS JULIA KRISTEVA - Muhafizah Muhafizah (Mafatih, 2021)
Abstract This article discusses the creation of nature in the Qur'an. As the title of this article suggests, the author is interested in explaining how the comparisons and differences in the creation of nature are found in the Qur'an, the Muslim book and the Tanakh, the Jewish book, because of the similarities between the two in explaining the creation of nature. Therefore, in this paper the author uses the intertextuality approach initiated by Julia Kristeva to compare the Qur'an and the Tanakh. The result of this paper from a structural point of view is the dominant overstatement equation, so that the parallel principle is slightly superior in the three sections, then the exception, haplology, and conversion principles are also found in each section. The fundamental difference lies in how the natural processes were created, in what stages they occurred, and the order in which the universe was created.